Business Networks and Performance: A Spatial Approach - Efthalia Dimara; Alexandra Goudi; Dimitris Skuras (European Regional Science Association (ERSA), 2003)
Business networks are associated to increased business performance and are regarded as a major factor influencing the development of rural and lagging areas. It is assumed that businesses access many networks in order to pursue their short and long term entrepreneurial objectives. The most important spatial features of this business-network relationship are firstly the spatial coverage of the network and secondly the location of the business in relation to its markets. As concerns the spatial coverage of the networks we distinguish between vertical and horizontal business networks. Vertical networks allow local enterprises to forge alliances with externally located consumers, suppliers, distributors, retailers and institutions, while horizontal networks provide relationships with locally based producers, institutions, and consumers. As concerns the location of the business in relation to its markets we distinguish between firms located in accessible locations and firms located in less accessible and peripheral locations in relation to their output markets. A survey of 160 businesses in the manufacturing and services sectors in two areas of Greece (one remote and one more accessible) is used to test empirically the effects of the spatial features of the business-network relationship on firm performance. Business performance is approximated through a series of measures capturing conventional firm growth and other less conventional managerial objectives. The analysis demonstrates that a significantly high proportion of successful businesses located in the remote area simultaneously access vertical and horizontal networks while in the less remote area successful businesses access mainly vertical networks. It is argued that policy initiatives towards the support of business networks as a tool of regional development policies should have a strong territorial and spatial perspective.
Keywords: 330